Growth Mindset and Professional Development among Early Childhood Educators: An Empirical Survey in Early Childhood Education Settings - Theresia Alviani Sum; Emilia Graciela Mega Taran (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Professional development for Early Childhood Education (ECE) teachers requires a growth mindset to address instructional challenges and limited access to training, particularly in rural areas. This study aims to examine the association between growth mindset and professional development orientation among ECE teachers in Manggarai Regency, East Nusa Tenggara, Indonesia. Using a descriptive quantitative survey approach, data were collected through a closed-ended Likert-scale questionnaire completed by 29 teachers. Data were analyzed using descriptive statistics (means, standard deviations, and score ranges) across four categories: growth mindset, professional engagement, reflective teaching, and perceived impacts on children’s behavior. The results indicate a strong growth mindset (M = 3.98) and high professional engagement (M = 4.03), although participation in learning communities varied; reflective teaching was also high (M = 3.94), and teachers reported increased children’s independence and learning enthusiasm (M = 3.98). These findings imply the need for context-specific training and strengthened teacher collaboration/learning communities to enhance reflective practice and improve the quality of ECE provision.